Numerical Study of Paraffin Wax Melting in a Cavity with A Gradient of Hot Wall Inclination - Korawan, Agus Dwi (UI Scholars Hub, 2020)
The melting of a phase change material (PCM) in a cavity with a gradient of hot wall inclination was simulated numerically using five models, namely, Model-A, Model-B, Model-C, Model-D, and Model-E with gradients of −2, −4, ∞, 4, and 2, respectively. The PCM was paraffin wax, which was melted using an enthalpy porosity technique with a pressure-based method. Model-A was found to be the best model. For the completion of the melting process, the models were assigned with the liquid fraction of 1. Model-A required the shortest time, followed by Model-B, Model-C, Model-E, and Model-D, respectively. Compared with Model-C, Model-A was 9.4% faster, Model-B was 3.8% faster, Model-D was 2.3% slower, and Model-E was 3.2% slower.